Pendugaan Umur Simpan Benih Padi (Oryza sativa L) Menggunakan Metode ASLT (Accelerated Shelf Life Testing)dengan Pendekatan Model Kadar Air Kritis - IPutu Mas Pradnyana Wibawa; Ida Bagus Putu Gunadnya; I Made Anom Sutrisna Wijaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
The purpose of this study was to prediction the shelf life of certified rice seeds using the ASLT (Accelerated Shelf Life Testing) method based on the critical moisture content approach. The varieties of rice seeds used in this research were Ciherang and Inpari 30 varieties which packed with polypropylene (PP) plastic packaging. The rice seeds packages were stored at environmental condition (temperature of 29 oC and RH of 75%). Observation on seeds germination was done daily until the seeds have a germination percentage below 80%. When the seeds under this condition, moisture content of the seeds was measured and refer as critical moisture content. It was found that the packaging permeability (k/x) of PP plastic was 0.013 gH2O/m2.day.mmHg. Observation on rice seed of Ciherang variety revealed that its values of initial moisture content (Ma) was 0.133 %, its critical moisture content (Mc) was 0.291 %, its total solid (Ws) was 8.8 kg, and pressure difference (ΔP) was 1,15 mmHg. While, for Invary 30 variety the values of its shelf life parameters were as follows: Ma 0.144 %, Mc 0.293 %, Ws 8.7 kg, and ΔP 0.9 mmHg. The prediction of shelf life the two certified rice seeds which were packed in PP plastic and stored at 29oC and RH of 75% were 156 days (5.03 months) for Ciherang variety and 254 days (8.19 months). ) for Inpari 30 variety.